Society of Behavioral Medicine Position Statement: promote sun-safety policies and practices for youth in educational, childcare, and recreational settings. Issue 2 (23rd August 2019) - Heckman, Carolyn J; Riley, Mary; Coups, Elliot J; Niu, Zhaomeng; Stapleton, Jerod L
Abstract : Youth should be allowed and encouraged to engage in sun-safe behaviors in educational, childcare, and recreational settings, including use of sunscreen, wide-brimmed hats, other sun-protective clothing, and shade.